Corrosion behavior and thermal cycle stability of TiNiTa shape memory alloy - Balci, E.; Dagdelen, F.; Mohammed, S. S.; Ercan, E. (Springer, 2022)
In this study, Ti50Ni30Ta20 (at/%) alloy, whose thermal, structural, mechanical properties and corrosion behavior was investigated, was produced by arc melting method. Some physical and chemical properties of the produced alloy such as thermal stability, phase transformation temperatures, thermal activation energies, microstructure, electrochemical corrosion resistance, microhardness were investigated. Thermal stability and A(austenite: B19(')) <-> M(martensite:B2) phase transition temperatures(PTT) were determined with the help of differential scanning calorimetry (DSC) at a heating-cooling rate of 10 degrees C min(-1). In addition, M -> A phase transition was proved during heating with the help of DTA/TG. The thermal activation energies of the alloy were calculated according to the Kissinger and Ozawa methods. The average thermal activation energy obtained according to these calculations was found to be 64.14 kJ mol(-1). In the optical microscope (OM) and SEM images, it was observed that the alloy consisted of an irregular dentritic structure at room temperature. As a result of the electrochemical analysis performed in SBF (artificial body fluid) at room temperature, the corrosion rate was calculated as 1.35 x 10(-3) mmpy and the corrosion resistance was found to be 0.071 M omega cm(2). In Vickers microhardness measurements, the microhardness of the alloy was taken from five different regions, and an average of 452 HV0.3 was found.
Keywords: Thermal activation energy; Corrosion resistance; Microhardness